Confronting racial and gender diference three approaches to multicultural counseling and therapy - Microtraining Associates ([Framingham, Mass.] : Microtraining Associates, 2004)
Presents several vignettes of counseling role-playing to demonstrate issues and techniques in multicultural counseling
Title from title screen
Keywords: Cross-cultural counseling -- United States; Multiculturalism -- United States; Counselors -- Training of -- United States